Case report: Emergency presentation of Meckel's diverticulum in the 3rd trimester of pregnancy - He, Yantao; Wang, Lilan; Cao, Wulan (Frontiers in Surgery, 2023)
Background: Symptomatic Meckel’s diverticulum (MD) is easily neglected in the acute abdomen during pregnancy. MD is the most common congenitally anomalous development of the intestines, with an incidence of 2% in the general population, although it is not easily diagnosed because of variable clinical features. Especially when complicated with pregnancy, doctors can easily overlook this disease, which directly threatens maternal and foetal life. Case Presentation: We report the case of a 25-year-old at 32 +2 weeks of gestation complicated with MD volvulus who presented with progressive abdominal pain and finally peritonitis. She underwent exploratory laparotomy and small-bowel resection. The mother and the baby successfully recovered. Conclusions: MD-complicated pregnancy is not easily diagnosed. Once highly suspiciously diagnosed, especially with peritonitis, surgery should be arranged, which helps preserve maternal and foetal life.